2011
DOI: 10.1371/journal.pone.0021999
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Prourokinase with Adjunctive C1-Inhibitor Is an Effective and Safer Alternative to tPA in Rat Stroke

Abstract: A single-site mutant (M5) of native urokinase plasminogen activator (prouPA) induces effective thrombolysis in dogs with venous or arterial thrombosis with a reduction in bleeding complications compared to tPA. This effect, related to inhibition of two-chain M5 (tcM5) by plasma C1-inhibitor (C1I), thereby preventing non-specific plasmin generation, was augmented by the addition of exogenous C1I to plasma in vitro. In the present study, tPA, M5 or placebo +/− C1I were administered in two rat stroke models. In P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
(65 reference statements)
3
10
0
Order By: Relevance
“…In fact the lysis time was shortened to 30 minutes, an effect that may have been related to conservation of M5 and plasminogen by the inhibitor. By contrast, fibrinolysis by the tPA alone was inhibited, as previously also found in vivo [ 28 ] ( Fig. 3B ).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In fact the lysis time was shortened to 30 minutes, an effect that may have been related to conservation of M5 and plasminogen by the inhibitor. By contrast, fibrinolysis by the tPA alone was inhibited, as previously also found in vivo [ 28 ] ( Fig. 3B ).…”
Section: Resultssupporting
confidence: 85%
“…2 ), whereas C1-inhibitor inhibited fibrinolysis by tPA ( Fig. 3B ), as also found previously in an animal model [ 28 ]. These optimally lytic doses of tPA are, of course, precluded clinically by ICH (1), especially in stroke where a further dose reduction is needed [ 7 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, as an alternative strategy, we found that M5, a mutant of native urokinase plasminogen activator (prouPA), can reduce infarct size with a reduced risk of bleeding. 39 …”
Section: Discussionmentioning
confidence: 99%
“…More recently, a single site mutant of prouPA has been developed which has the advantage of being five-fold more stable in plasma at therapeutic concentrations, making it much less likely to cause bleeding side effects. At the same time, it has all the other properties of native prouPA [19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%